MANAJEMEN PROGRAM PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) DI SMA NEGERI 1 PEKANBARU - Wahyuningsih Budi Astuti; Zulfan Saam; Isjoni Isjoni (Universitas Riau, 2019)
The aim of this research is how management of program the information center and counseling youth at SMAN 1 Pekanbaru with subfokus are: (1) Achievement of vision and mission implementation of program the information center and counseling youth at SMAN 1 Pekanbaru (2) Planning of program the information center and counseling youth at SMAN 1 Pekanbaru (3) Organizing of program the information center and counseling youth at SMAN 1 Pekanbaru (4) Implementation of program the information center and counseling youth at SMAN 1 Pekanbaru (5) Supervision of program the information center and counseling youth at SMAN 1 Pekanbaru (6) The result of program the information center and counseling youth at SMAN 1 Pekanbaru. The approach of this research is qualitative gotten from respondents with data collection technique through documentation, observation, and in-depth interview. Further data analysis through data reduction, display data, conclusion and verification. The results showed that (1) Achievement of vision and mission implementation of program the information center and counseling youth at SMAN 1 Pekanbaru is categorized sufficient because it has fulfilled 3 aspects of 5 aspects from the objective standard (2) Planning of program the information center and counseling youth at SMAN 1 Pekanbaru is categorized good because it has fulfilled 4 aspects of the 5 aspects from the objective standard (3) The organization of program the information center and counseling youth at SMAN 1 Pekanbaru is categorized very well because it has fulfilled 5 aspects of 5 aspects from the objective standard (4) Implementation of program the information center and counseling youth at SMAN 1 Pekanbaru is categorized well because it has fulfilled 4 aspects of 5 aspects from the objective standard (5) Supervision of program the information center and counseling youth at SMAN 1 Pekanbaru is categorized sufficient because it has fulfilled 3 aspects from 5 aspects from the objective standard (6 ) The result of program the information center and counseling youth in SMAN 1 Pekanbaru is categorized less because it has fulfilled 2 aspects of 5 aspects from objective standard.